2016
DOI: 10.1080/14763141.2016.1159323
|View full text |Cite
|
Sign up to set email alerts
|

Knee joint position sense of roller hockey players: a comparative study

Abstract: This study aimed to compare knee joint position sense of roller hockey players with an age-matched group of non-athletes. Forty-three male participants voluntarily participated in this cross-sectional study: 21 roller hockey players (mean age: 23.2 ± 4.2 years old, mean weight: 81.8 ± 9.8 kg, mean height: 180.5 ± 4.1 cm) and 22 age-matched non-athletes (mean age: 23.7 ± 3.9 years old, mean weight: 85.0 ± 6.2 kg, mean height: 181.5 ± 5.0 cm). Knee joint position sense of the dominant limb was evaluated using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…This is supported by previous research which found that dancers demonstrate greater JPS performance at lower (1.5–2.5 times) [ 51 ] and upper (up to 3 times) limbs [ 52 , 53 ] compared with untrained people. Also, athletes of other sports not associated with aesthetics and the control of body segments in space were shown to have 2.7 times better active JPS performance [ 54 ]. Furthermore, Pánics et al [ 24 ] showed that proprioceptive training resulted in up to 2.5 times greater JPS performance among handball players.…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by previous research which found that dancers demonstrate greater JPS performance at lower (1.5–2.5 times) [ 51 ] and upper (up to 3 times) limbs [ 52 , 53 ] compared with untrained people. Also, athletes of other sports not associated with aesthetics and the control of body segments in space were shown to have 2.7 times better active JPS performance [ 54 ]. Furthermore, Pánics et al [ 24 ] showed that proprioceptive training resulted in up to 2.5 times greater JPS performance among handball players.…”
Section: Discussionmentioning
confidence: 99%
“…In another study of wrist proprioception, an absolute error of 4.7° ± 0.3° was measured when participants were asked to actively reproduce the wrist configuration previously reached after a movement executed by a robotic device [ 46 ]. For the lower extremity, Venancio et al evaluated knee position sense by looking at the angular differences between an initial reference position and the position actively reproduced by healthy participants [ 47 ]. After three trials, a mean relative error of 5.8° ± 4.4° was obtained while targeting angular positions located between 40° and 60° of knee flexion.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding game characteristics, observational instruments are explored to understand game patterns [14,26]. The high-intensity demands of the game combined with the mastery of skating and ball possession are described as potential injury risk [21,27,28].…”
Section: General Description Of the Studiesmentioning
confidence: 99%
“…The implications of groin pain were analyzed during Christiania stop (a sudden and intense change of direction and stopping) in professional rink-hockey players during a simulated test [27]. The influence of the knee joint position sense in rink-hockey players was studied, relevant information about the angular errors and benefits on proprioceptive accurate have been reported [28] (see Table 4). With no approach run, the ball speed may reach 90 ± 5.2 km/h (2nd league) and 102.0 km/h ± 4.6 (1st league).…”
Section: Injuries In Rink-hockeymentioning
confidence: 99%
See 1 more Smart Citation